Glucose metabolism, islet architecture, and genetic homogeneity in imprinting of [Ca2+](i) and insulin rhythms in mouse islets. - Craig S Nunemaker; John F Dishinger; Stacey B Dula; Runpei Wu; Matthew J Merrins; Kendra R Reid; Arthur Sherman; Robert T Kennedy; Leslie S Satin (PLoS ONE, 2009)
We reported previously that islets isolated from individual, outbred Swiss-Webster mice displayed oscillations in intracellular calcium ([Ca2+](i)) that varied little between islets of a single mouse but considerably between mice, a phenomenon we termed "islet imprinting." We have now confirmed and extended these findings in several respects. First, imprinting occurs in both inbred (C57BL/6J) as well as outbred mouse strains (Swiss-Webster; CD1). Second, imprinting was observed in NAD(P)H oscillations, indicating a metabolic component. Further, short-term exposure to a glucose-free solution, which transiently silenced [Ca2+](i) oscillations, reset the oscillatory patterns to a higher frequency. This suggests a key role for glucose metabolism in maintaining imprinting, as transiently suppressing the oscillations with diazoxide, a K(ATP)-channel opener that blocks [Ca2+](i) influx downstream of glucose metabolism, did not change the imprinted patterns. Third, imprinting was not as readily observed at the level of single beta cells, as the [Ca2+](i) oscillations of single cells isolated from imprinted islets exhibited highly variable, and typically slower [Ca2+](i) oscillations. Lastly, to test whether the imprinted [Ca2+](i) patterns were of functional significance, a novel microchip platform was used to monitor insulin release from multiple islets in real time. Insulin release patterns correlated closely with [Ca2+](i) oscillations and showed significant mouse-to-mouse differences, indicating imprinting. These results indicate that islet imprinting is a general feature of islets and is likely to be of physiological significance. While islet imprinting did not depend on the genetic background of the mice, glucose metabolism and intact islet architecture may be important for the imprinting phenomenon.